Generasi Milenial dalam Seni Lukis Kontemporer - Ari Nopri; Yasrul Sami (Journal on Education, 2023)
The purposed of this final ending works is to remind to re-awaken to millennial generation about a consumptive lifestyle in everyday life. The characteristics of the millennial generation that tend to be impulsive and sensitive to a new innovations supported the tendency of a consumptive millenials lifestyle. With that, millennials who go to cafes are not because they needed it but because they want to it. Through this, millennials often exposed their presence to the spot to social networks, while in cafes. The method and process of creating this works is carried out in turns, namely: the prepared stage, elaborated, synthesis, concept realization, until the stage of completion or finishing the process in the work. Ten works were depicted with sizes of 110 cm x 100 cm and 100 x 100 cm with oil on canvas as the medium with different titles, namely: " Mind " , " Consistent " , " Information " , " Killing me inside " , " Undercover ” , “Affected” , “Guess” , “Freedom” , “Technology”,